2011
DOI: 10.1366/10-06150
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering (SERS) Detection of Low Concentrations of Tryptophan Amino Acid in Silver Colloid

Abstract: The surface-enhanced Raman scattering (SERS) spectrum of L-tryptophan has been studied in the concentration range 1.4 × 10(-8) to 5 × 10(-4) M. A borohydride-reduced silver colloid was employed as the nanoparticle enhancing agent and different electrolytes have been tested for activation of the colloid. The optimum conditions have been determined for achieving high sensitivity of detection. The experimental procedure developed, which includes the use of a composite electrolyte (a mixture of NaHCO(3) and NaCl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…An example is spectrum (b) in Figure 2. We have to note that our SERS spectra of tryptophan are completely different than that obtained by Aliaga et al [10] from the same SERS system (dried hydroxylamine-reduced Ag colloid/tryptophan drop) but in good agreement with Raman spectra measured from Ag colloidal solutions [11,12] and solid powder [12]. In Figure 2, spectrum (b), only spectral bands that can be surely assigned to tryptophan are marked [12].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…An example is spectrum (b) in Figure 2. We have to note that our SERS spectra of tryptophan are completely different than that obtained by Aliaga et al [10] from the same SERS system (dried hydroxylamine-reduced Ag colloid/tryptophan drop) but in good agreement with Raman spectra measured from Ag colloidal solutions [11,12] and solid powder [12]. In Figure 2, spectrum (b), only spectral bands that can be surely assigned to tryptophan are marked [12].…”
Section: Resultssupporting
confidence: 75%
“…SERS spectra of tryptophan obtained using Ag colloids have been reported in the literature recently [10][11][12], but the results significantly differ from each other. Such discrepancy can be explained by particular experimental conditions (pH, used Ag colloid and its activation, mode of adsorption, and consequently orientation of tryptophan on the surface, etc.).…”
Section: Resultsmentioning
confidence: 85%
“…These spectra show successful binding of Trp and Trp-d5 to the surface and are similar to other previous studies that investigated unlabelled Trp. 25,52 It is clear that some of the bands are shi ed to lower wavenumbers due to the presence of the heavier isotopes of Trp-d5. Peaks at 1122, 1228 and 1600 cm 1 , assigned to phenyl CH bending vibration, phenol ring breathing and indole ring According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, recent studies have demonstrated the application of SERS for the detection and quanti cation of Trp and caff eine with high levels of sensitivity and reproducibility. 25,26 Alharbi et al concluded that SERS can be used to identify long-term abuse of illicit materials as well as determine accurate drug dosing for legal therapeutics. Furthermore, Chen and colleagues reported the interaction of caff eine molecules with diff erent colloids at various concen-trations.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Silver and gold colloids have also been analyzed using different sizes, preparation methods, and concentrations of analyte or reporter molecules attached to the nanoparticle. [18][19][20][21][22] To increase the Raman scattering event probability further, various mechanical methods have been used to make the nanoparticles aggregate together, which causes strong enhancements to occur. 23 One mechanical aggregation method was that of Hwang et al, in which an optoelectrofluidic device was used to create plasmonic aggregates aligned at the laser beam spot and produce strong enhancements.…”
Section: Introductionmentioning
confidence: 99%